Analysis of Student's Response toward The Types of Written Corrective Feedback Used by The English Teachers at SMAN I Tiumang - Widia Siska; Nidya Fitri (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to determine the type of written correction used by the teacher in the writing of class XI students of SMAN 1 Tiumang, Dharmasraya Regency and student responses to feedback corrections. This type of research is qualitative. The data collection technique used is Cluster Random Sampling. Research instruments are documents and questionnaires. The sample taken in this study was students XI IPA 1, a total of 26 students. The document "Writing Assignments "is used to find the type of written correction used by the teacher. Researchers analyzed 26 student documents and asked students to fill out a questionnaire. This document is analyzed according to the type of correction used by the teacher, namely, direct corrective feedback and indirect corrective feedback. The questionnaire is formulated on the basis of indicators in the component of student responses to the written correction of the teacher. The results of this study are 1) Teachers use both types of direct and indirect corrections to provide feedback on student writing, but more predominantly teachers use indirect corrections and 2) students have a good response to corrections to feedback given by the teacher.